Surveying physical therapists' understanding of benign paroxysmal positional vertigo - Harrell, Regan G.; Hart, Rebecca; Jen, Joanna C.; Whitney, Susan L. (Frontiers in Rehabilitation Sciences, 2023)
Introduction Benign paroxysmal positional vertigo (BPPV) is a common condition with disabling symptoms that is diagnosed and effectively treated at the bedside. Our encounter with patients experiencing prolonged BPPV who may not have received appropriate physical therapy prompted us to explore barriers to the diagnosis and treatment for BPPV among physical therapists, which has not been extensively investigated. We hypothesize that a potential barrier may be a lack of understanding of subtle symptoms of BPPV that deviate from the classical presentation. The gold standard for diagnosing definite BPPV is subjective dizziness or vertigo with nystagmus in response to positional testing. There are variants of BPPV including subjective BPPV (subjective dizziness or vertigo without nystagmus) and vestibular agnosia (nystagmus without subjective dizziness or vertigo) that do not meet the diagnostic criteria for definite BPPV but are equally responsive to the same repositioning maneuvers. The purpose of this project was to survey physical therapists for their understanding of BPPV including subjective BPPV and vestibular agnosia. Methods A panel of experts created a 16-question survey, designed for physical therapists, with three categories: (1), inquiring if they treat persons with BPPV, (2) three clinical vignettes for definite BPPV, subjective BPPV, and BPPV with vestibular agnosia, and (3) demographic information. Data collection occurred at two large physical therapy meetings, one of which was a national professional meeting and the other was a professional continuing medical education course geared towards advancing vestibular rehabilitation skills. Results There were 426 people who completed the survey, 364 of whom treat BPPV in their practice. In the first clinical vignette created to assess the respondents' understanding of definite BPPV, 229 (62%) of respondents would always assess a patient for BPPV based on complaints of a “room spinning” vertigo from head movement. When asked if the complaint was lingering “lightheadedness or feelings of imbalance” from head movement, only 158 (43%) reported they would perform positional testing to reassess. In the BPPV variant vignettes, 187 (51%) identified the patient with subjective BPPV as having BPPV and 305 (85%) identified the patient with vestibular agnosia as having BPPV. Discussion The results of this survey demonstrate gaps in knowledge regarding BPPV across practice settings and experience, with opportunities to bridge these gaps to improve treatment for BPPV.